2020
DOI: 10.1007/jhep08(2020)018
|View full text |Cite
|
Sign up to set email alerts
|

Worldline master formulas for the dressed electron propagator. Part I. Off-shell amplitudes

Abstract: In the first-quantised worldline approach to quantum field theory, a longstanding problem has been to extend this formalism to amplitudes involving open fermion lines while maintaining the efficiency of the well-tested closed-loop case. In the present series of papers, we develop a suitable formalism for the case of quantum electrodynamics in vacuum (part one and two) and in a constant external electromagnetic field (part three), based on second-order fermions and the symbol map. We derive this formalism from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 182 publications
(277 reference statements)
1
43
1
Order By: Relevance
“…These experiments are characterized, to a very good approximation, by a single, well-known baseline. In [3], we found, for RENO and Daya Bay data, nontrivial correlations between sin 2 θ 13 , |∆m 2 31 | and the decoherence parameter σ. Future JUNO data, in the absence of strong decoherence effects, are expected to significantly weaken these correlations.…”
Section: Jhep06(2021)042mentioning
confidence: 77%
See 3 more Smart Citations
“…These experiments are characterized, to a very good approximation, by a single, well-known baseline. In [3], we found, for RENO and Daya Bay data, nontrivial correlations between sin 2 θ 13 , |∆m 2 31 | and the decoherence parameter σ. Future JUNO data, in the absence of strong decoherence effects, are expected to significantly weaken these correlations.…”
Section: Jhep06(2021)042mentioning
confidence: 77%
“…We refer to [3] for a more careful discussion of these parameters and their effects. If no loss of coherence occurs during neutrino propagation, ξ jk (= ξ kj ) = 0.…”
Section: Jhep06(2021)042mentioning
confidence: 99%
See 2 more Smart Citations
“…Systematic rules which generalise a string-based computation of field-theory amplitudes were developed by Bern and Kosower [31], and it was shown that they can also be directly derived from the Schwinger worldline formalism as derived by Bern and Dunbar [32]. As a computational alternative to Feynman diagrams worldline approaches maintain significant interest [33,34] providing a context to study asymptotic states in scattering problems [35], and for computing gravitational-radiation contributions to black-hole scattering [36].…”
Section: Jhep04(2021)276mentioning
confidence: 99%